"A Sense of Where You Are, " Bowling Alone, and the Future of the Society of Clinical Psychology. (December 2015) - Keane, Terence M.
Abstract : Professional organizations in all specialties are experiencing membership declines largely as a function of the demands on young graduates to see benefits and advantages to membership. This response to the Robiner et al. (2015) article highlights the importance of professional organizations, what they do for the profession, and what benefits these organizations confer at the individual level.